A web-based carepartner-integrated rehabilitation program for persons with stroke: study protocol for a pilot randomized controlled trial - Sarah Blanton (Pilot and Feasibility Studies, 2019)
Abstract Background Family carepartner management and support can improve stroke survivor recovery, yet research has placed little emphasis on how to integrate families into the rehabilitation process without increasing negative carepartner outcomes. Our group has developed creative approaches for engaging family carepartners in rehabilitation activities to improve physical and psychosocial health for both the carepartner and stroke survivor. The purpose of this study is to explore a novel, web-based intervention (Carepartner and Constraint-Induced Therapy; CARE-CITE) designed to facilitate positive carepartner involvement during a home-based application of constraint-induced movement therapy (CIMT) for the upper extremity. Methods The primary aim of the study is to determine feasibility of CARE-CITE for both stroke survivors and their carepartners. Carepartner mental health, family conflict surrounding stroke recovery, and stroke survivor upper extremity function will be evaluated using an evaluator blinded, two-group experimental design (blocked randomization protocol according to a 2:1 randomization schema) with 32 intervention dyads and 16 control dyads (who will receive CIMT without structured carepartner involvement). CARE-CITE consists of online education modules for the carepartner to review in parallel to the 30-h CIMT that the stroke survivor receives. The intent of CARE-CITE is to enhance the home-based intervention of CIMT, by helping the carepartner support the therapy and create a therapeutic home environment encouraging practice of the weaker arm in functional tasks. Discussion The CARE-CITE study is testing the feasibility of a family-integrated rehabilitation approach applied in the home environment, and results will provide the foundation for larger clinical studies. The overall significance of this research plan is to increase the understanding and further development of interventions that may serve as models to promote family involvement in the rehabilitation process. Trial registration ClinicalTrials.gov, NCT02703532. Registered 9 March 2016